The Relationship between Entrepreneurial Self-Efficacy and Entrepreneurial Intention among University Students - Wijangga, Jennifer; Sanjaya, Ersa Lanang (Universitas Ciputra Surabaya, 2019)
This study aims to determine the relationship between self-efficacy in entrepreneurship with entrepreneurial intentions among university students, specifically for those who are in their final semester. As for its research method, this study uses a quantitative method to explain the relationship between variables by collecting data that has been distributed to 104 respondents. The research instrument for this study is a scale of entrepreneurial self-efficacy and an entrepreneurial intention scale, both of which meet reliability requirements. The result of the study states that there is a positive and significant relationship between self-efficacy entrepreneurship and entrepreneurial intentions.